2005
DOI: 10.1007/s11104-004-2297-6
|View full text |Cite
|
Sign up to set email alerts
|

Response of soil δ15N and nutrients to eastern red cedar (Juniperus virginiana) encroachment into a relict calcareous prairie

Abstract: The calcareous prairies of Louisiana have been threatened by the encroachment of woody plants, primarily eastern red cedar (Juniperus virginiana). The restoration and management of these rare plant communities require a thorough understanding of the soils supporting them. The knowledge of whether eastern red cedar encroachment has altered these soils is also of interest. We studied the depth distribution, at contrasting vegetation types (prairie, transition, forest) and landscape positions, of d 15 N, total N,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Although the eastern redcedar is reputed to be able to tolerate a wide range of soil types, it has been widely observed that there are noticeable differences in their phenotypes on different soils [ 25 , 26 , 62 ]. High abundance of nutrients such as nitrogen may also be important for niche expansion of eastern redcedar, especially in old fields that were usually fertilized [ 20 , 40 , 42 , 47 , 49 , 68 , 69 , 114 ]. Furthermore, a combination of shade and nitrogen fertilization may facilitate tree invasions of grasslands [ 115 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although the eastern redcedar is reputed to be able to tolerate a wide range of soil types, it has been widely observed that there are noticeable differences in their phenotypes on different soils [ 25 , 26 , 62 ]. High abundance of nutrients such as nitrogen may also be important for niche expansion of eastern redcedar, especially in old fields that were usually fertilized [ 20 , 40 , 42 , 47 , 49 , 68 , 69 , 114 ]. Furthermore, a combination of shade and nitrogen fertilization may facilitate tree invasions of grasslands [ 115 ].…”
Section: Discussionmentioning
confidence: 99%